Assessing the Quality and Potential Efficacy of Commercial Extracts of Rhodiola rosea L. by Analyzing the Salidroside and Rosavin Content and the Electrophysiological Activity in Hippocampal Long-Term Potentiation, a Synaptic Model of Memory - Dimpfel, Wilfried; Schombert, Leonie; Panossian, Alexander G. (Frontiers in Pharmacology, 2018)
Rhodiola rosea L. roots and rhizome extracts are active ingredients in adaptogenic herbal medicinal products (HMP) and dietary supplements for temporary relief of symptoms of stress, such as fatigue and weakness. R. rosea extract has a stimulating effect on the CNS, suggesting potential benefits on cognitive functions, memory, learning, and attention. The reproducible efficacy and quality of preparations of the underground parts of R. rosea depend on the highly variable content of the active markers, salidroside and rosavin, which affect the quality of HMP and dietary supplements. However, it is not clear which analytical markers are important for assessing the efficacy of R. rosea preparations intended for use in aging-induced mild cognitive disorders, such as attenuated memory, attention, and learning. Furthermore, the activity of various commercial R. rosea extracts has not been correlated with their content. Here, the biological activities of salidroside, rosavin, and seven commercial extracts of underground parts of R. rosea were assessed using a synaptic model of memory: long-term potentiation (LTP) of synaptic transmission in hippocampus slices. A high degree of variation in the content of all active markers was observed. One extract from China lacked rosavin, and there was even variation in the extracts from the Altai geographic region. In vitro, rosavin, salidroside and all tested R. rosea extracts potentiated electric stimulation of an intra-hippocampal electric circuit, which resulted in higher responses of the pyramidal cells in isolated hippocampus slices. Rosavin was more active at higher concentrations than salidroside; while, salidroside was more effective at lower concentrations. The highest content of both active markers was found in the extracts that were active at the lowest concentrations tested; while, some extracts contained some other compounds that presumably reduced the efficacy due to antagonistic interactions. Standardized content of active markers is necessary for the quality control of herbal preparations containing R. rosea extracts, but insufficient for assessment of their potential efficacy. Additional bioassays are needed to assure the reproducible pharmacological activity of R. rosea extracts; therefore, the LTP of synaptic transmission in hippocampus slices may serve as a validation tool for the quality control of R. rosea extracts.